How many low birthweight babies in low- and middle-income countries are preterm? - Fernando C Barros; Aluísio J D Barros; José Villar; Alicia Matijasevich; Marlos R Domingues; Cesar G Victora (Revista de Saúde Pública)
OBJECTIVE: To assess the prevalence of preterm birth among low birthweight babies in low and middle-income countries. METHODS: Major databases (PubMed, LILACS, Google Scholar) were searched for studies on the prevalence of term and preterm LBW babies with field work carried out after 1990 in low- and middle-income countries. Regression methods were used to model this proportion according to LBW prevalence levels. RESULTS: According to 47 studies from 27 low- and middle-income countries, approximately half of all LBW babies are preterm rather than one in three as assumed in studies previous to the 1990s. CONCLUSIONS: The estimate of a substantially higher number of LBW preterm babies has important policy implications in view of special health care needs of these infants. As for earlier projections, our findings are limited by the relative lack of population-based studies.